Biological perspectives in geotechnics: theoretical developments - Jain, Surabhi; Mishra, Partha Narayan; Tiwari, Satyam; Wang, Yijie; Jiang, Ningjun; Dash, Hirak Ranjan; Chang, Ilhan; Kumar, Ashutosh; Das, Sarat Kumar; Scheuermann, Alexander; Bore, Thierry (Reviews in Environmental Science and Biotechnology, 2023)
The interaction of bio–geosphere dates to the formation of first unicellular microbes on earth. However, it is only relatively recently that the complex biological interactions are observed, characterised, and simulated for its use in the domain of geotechnical engineering. Also, many bioinspired approaches have been utilised in computational geotechnics for optimisation and data analysis process. The living phase present in the soil system hold a bearing on the majority of geochemical reactions and assist in modifying its fundamental and engineering behaviour. It necessitates revaluation and rescrutinisation of the conventional theories and formulations in geotechnical engineering, where soil has always been considered as an inert engineering material from biological perspective. To that end, this manuscript provides a critical review on biological approaches used in geotechnical engineering by highlighting the ongoing developments, achievements, and challenges to implement the processes. The review further emphasises the role of biological systems on the alteration of fundamental properties of soils and their consequences on effective stress, strength and stiffness, volume change and conduction properties of soils. Overall, the manuscript provides a basic understanding on the biological intervention in the soil system and the importance of consideration of the fourth phase in the soil system, i.e., the living phase, while describing such interventions.
Keywords: Biogeotechnics; Bioinspired approaches; Biomediation; Conduction; Effective stress; Shear strength; Volume change